Stereoselectivity of In Vivo Processes and Bioactivity of Farrerol Enantiomers - Lirong Chen; Tang Yan; Dongting Huang; Wei Xu; Yongjing Liu; Xiaoying Wang; Hua Li (Molecules)
Farrerol, a bioactive compound found in Folium Rhododendri daurici, demonstrates various biological and pharmacological effects. Nevertheless, the stereoselectivity of in vivo processes and bioactivity between its enantiomers have not been thoroughly investigated. This study aimed to explore the stereoselectivity and pharmacological activity variations in farrerol enantiomers, focusing on stereoselective pharmacokinetics, tissue distribution, in vitro metabolism using liver microsomes, in vivo intestinal absorption, molecular simulations of binding affinity with antiproliferative target, and cell viability assessed through the CCK-8 assay. The findings indicated that the pharmacokinetic characteristics of farrerol in rats’ plasma, liver, and kidney tissues displayed enantioselectivity after intragastric administration. Then, no chiral transformation between farrerol enantiomers was observed in the rat plasma when (+)-farrerol and (−)-farrerol were orally administered. Additionally, there are notable stereoselective differences in the inhibition of CYP 1A2, CYP 2C9, CYP 2C19, and CYP 3A4/5 enzymes by (+)-farrerol and (−)-farrerol (p < 0.01). These differences may contribute to the stereoselectivity observed in the hepatic metabolism of the two enantiomers of farrerol. In addition, there were selective differences in the binding of farrerol enantiomers to anti-proliferative targets, including UCHL3, STAT3β, PTP1B, and GSK3β. Farrerol enantiomers exhibited similar growth inhibitory effects in HT-29 cell. Overall, our work will provide a solid theoretical basis and experimental reference for the further development and utilization of farrerol enantiomers.